Menyelami Peran Metode Pembelajaran dalam Transformasi Pendidikan: Potensi dan Tantangan untuk Generasi Emas - Zidan Fajri; Husni Hamdani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research investigates the role of teachers in creating transformative education, with the aim of shaping the Golden Generation. The study utilizes a qualitative approach to explore various aspects of this process, focusing on the contributions of teachers in reshaping the educational landscape to meet the needs of future generations. The research methodology employed is qualitative descriptive, aiming to uncover new meanings, explain conditions, determine event frequencies, and categorize information. Data is collected through a literature review from various online sources such as books, journals, and relevant references. The findings of the research indicate that teachers are responsible not only for imparting knowledge but also for developing students' critical thinking, creativity, and adaptability skills. The study highlights the importance of innovative teaching methods, teacher professionalism, and educational ecosystem support in preparing students to face future challenges. As a preemptive step towards the Golden Generation, the research emphasizes continuous collaboration among educators, policymakers, and stakeholders to create an educational environment that fosters students' holistic development. The results of this research contribute to the discourse on educational transformation and provide guidance for pedagogical practices aligned with the aspirations of future generations.